Seamless interoperability in logistics by ontology alignment - Mohammadi, Majid; Hofman, Wout; Tan, Yao-Hua (Journal of Supply Chain Management Science, 2020)
This paper is dedicated to applying ontology alignment systems to the heterogeneity problem in logistics. The primary motivation for doing so is to enable interoperability among different IT systems in logistics, all with their own database scheme. We first analyze different standards for logistics interoperability, which are implemented by XML schema definition (XSD) or Electronic Data Interchange (EDI) with implicit and inconsistent semantics across these open standards. To analyze the applicability of ontology alignment, we create two ontologies from two well-known standards that are rich in terms of semantic relations between entities. These ontologies are subjected to the state-of-the-art alignment systems, applying matching with and without logistics background knowledge. Our experimental analyses show that the alignment using background knowledge with some annotations finds better mappings between the given logistics standards and is thus applicable to real-world situations under particular conditions.